2014
DOI: 10.3389/fimmu.2014.00370
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Therapeutic Tools in Cardiovascular Diseases

Abstract: Extracellular vesicles (EVs), including microvesicles (MVs) and exosomes, are small vesicles secreted from a wide variety of cells. Whereas MVs are particles released by the outward budding of the plasma membrane, exosomes are derived from endocytic compartments. Secretion of EVs can be enhanced by specific stimuli, and increased plasma circulating levels of EVs have been correlated with pathophysiological situations. MVs, already present in the blood of healthy individuals, are considerably elevated in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 86 publications
(108 reference statements)
1
82
0
Order By: Relevance
“…EVs, particularly exosomes, have attracted considerable interest for their potential use both as biomarkers and as vehicles for gene (or pseudogene) therapy . They are found in the circulation in healthy individuals, and their number rises in several CV conditions associated with inflammation; a growing number of reports have been documenting a role for them in endothelial function regulation .…”
Section: Therapeutic Potential Of Exosome/ Microvesicle‐contained Mirmentioning
confidence: 99%
“…EVs, particularly exosomes, have attracted considerable interest for their potential use both as biomarkers and as vehicles for gene (or pseudogene) therapy . They are found in the circulation in healthy individuals, and their number rises in several CV conditions associated with inflammation; a growing number of reports have been documenting a role for them in endothelial function regulation .…”
Section: Therapeutic Potential Of Exosome/ Microvesicle‐contained Mirmentioning
confidence: 99%
“…These results indicated that EPC-EVs fused with the cells and were degraded by the Golgi apparatus, releasing their cargo along the way. However, it was not possible to demonstrate an association between EPC-EVs and lysosomes, which have been suggested to digest EVs (29).…”
Section: Epc-derived Extracellular Vesicle Isolationmentioning
confidence: 84%
“…Exosome treatments have several advantages over the gene‐based therapies. Utilization of exosomes reduces immunogenicity and toxicity caused by biomaterial treatment, such as nanoparticles (Fleury et al, ). Qi et al reported that exosomes secreted from human induced pluripotent stem cell‐derived mesenchymal stem cells could accelerate critical‐sized bone defects healing by enhancing the proliferation and osteogenic differentiation of bone marrow MSCs derived from ovariectomized (OVX) rats (rBMSCs‐OVX) (Qi et al, ).…”
Section: Discussionmentioning
confidence: 99%